Do web-based competitions promote physical activity? Randomized controlled trial. (March 2017) - Prestwich, Andrew; Conner, Mark; Morris, Ben; Finlayson, Graham; Sykes-Muskett, Bianca; Hurling, Robert
Abstract: Objectives: Introducing competitions may inspire positive behaviour change but they tend to be implemented alongside other strategies. Thus, the study examined the effectiveness of a competitive web-based intervention to promote physical activity, disentangled the effects of competition from other behaviour change techniques, and identified underlying mediators. Design: Randomized controlled trial. Methods: Physically inactive adults living or working in a UK city ( n = 281) were recruited. Participants were randomized to one of three web-based conditions: a control group; a group encouraged to self-monitor their steps and who received basic feedback; a group encouraged to self-monitor their steps who received basic feedback plus additional feedback to instigate competition. Participants' physical activity was monitored through pedometers for one-week pre-intervention and for four-weeks during the intervention period. Participants completed the BREQ-2 and measures of intention, planning, goal conflict, goal importance, effort, commitment, perceived behavioural control and self-efficacy pre- and post-intervention. Results: Participants in the competition condition increased their steps significantly more than those in the control group with the effect being mediated by increased goal importance, identified motivation and intrinsic motivation. Participants in the competition condition increased their steps more than those in the self-monitoring condition. There was weaker evidence that the self-monitoring group increased their steps more than those in the control condition. Conclusions: Self-monitoring and feedback can increase physical activity but adding a competitive component, implemented via the web, can boost goal importance, identified motivation and intrinsic motivation that mediate these increases in physical activity. Highlights: This study isolates the unique effect of competition on physical activity promotion. Competition increased physical activity relative to self-monitoring and control. Competition effects mediated by motivation (identified, intrinsic, importance). Self-monitoring with basic feedback had limited effects on physical activity.